Fearless Dominance and reduced feedback-related negativity amplitudes in a time-estimation task – Further neuroscientific evidence for dual-process models of psychopathy() - Schulreich, Stefan (Elsevier Science B.V, 2013)
Dual-process models of psychopathy postulate two etiologically relevant processes. Their involvement in feedback processing and its neural correlates has not been investigated so far. Multi-channel EEG was collected while healthy female volunteers performed a time-estimation task and received negative or positive feedback in form of signs or emotional faces. The affective-interpersonal factor Fearless Dominance, but not Self-Centered Impulsivity, was associated with reduced feedback-related negativity (FRN) amplitudes. This neural dissociation extends previous findings on the impact of psychopathy on feedback processing and further highlights the importance of distinguishing psychopathic traits and extending previous (neuroscientific) models of psychopathy.